Board diversity and corporate social performance: Does the family firm status matter?. (15th March 2021) - Veltri, Stefania; Mazzotta, Romilda; Rubino, Franco Ernesto
Abstract: The aim of the study is to investigate whether the board of directors (BoD) diversity affect corporate social performance (CSP), an alternative measure of corporate performance based on social outcomes. The article distinguishes between a structural diversity of boards (proxied by director independence), and a demographic diversity in boards (proxied by gender diversity) and our concept of CSP. The sample is constituted of the firms listed to the FTSE‐MIB index, which comprehends the most Italian capitalized listed firms. The analysis, covering a ten‐year period (2010–2019), provides evidence that independent directors positively affect CSP and that gender has no effect on CSP. We also tested the association between BoD and CSP separately for family firms (FFs) and non‐family firms (NFFs) to investigate whether FF status is a contingent condition modifying the effect of board features on CSP. Our result provide evidence of it.